PEMBUATAN DAN UJI AKTIVITAS SEDIAAN UNGUENTA SCARLESS WOUND HEALING DENGAN EKSTRAK BINAHONG (Anredera cordifolia (Ten) Steenis) DAN ZAT AKTIF ANTIINFLAMASI NATRIUM DIKLOFENAK - Bertha Nathania; Sri Hartati Yuliani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2015)
Wounds often leave scars that interfere with skins aesthetic, even lead to health problems, in some of people, scars tend to grow excessively cause of keloid scarring or cuts. One of the causes of scarring wounds is the process of long-term inflammation. Diclofenac sodium is a bitter taste substances. Diclofenac sodium is a selective inhibitor, which inhibit COX-2 in inflammatory processes. Binahong (Anredera cordifolia) is one of the plants in Indonesia, which came from China. Binahong leaves contain saponins, flavonoids, namely quinon, steroids, monoterpenoid, and sesquiterpenoid which has been known as a wound healer. The making of ointment scarless wound healing dosage form is by combining binahong leaves extract and the addition of anti-inflammatory agent diclofenac sodium (F4), which expected to reduce the wound scar on the Switzerland Webster strain mices skin that has bleed with incision method. The test that has been used is histopathology test followed by an extensive calculation of collagen. The calculation data were analyzed using T-test with 95% confidence level. The results from this research indicate that ointment of binahong extract and diclofenac sodium (F4) produce less scar.